Comparative Study between Activated Carbon and Charcoal for the Development of Latent Fingerprints on Nonporous Surfaces - Hameed, Hadeel Faroak; Mohammed, Alaa K.; Zageer, Dheaa S. (Al-Khwarizmi Engineering Journal, 2022)
For criminal investigations, fingerprints remain the most reliable form of personal identification despite developments in other fields like DNA profiling. The objective of this work is to compare the performance of both commercial charcoal and activated carbon powder derived from the Alhagi plant to reveal latent fingerprints from different non-porous surfaces (cardboard, plain glass, aluminum foil sheet, China Dish, Plastic, and Switch). The effect of three variables on activated carbon production was investigated. These variables were the impregnation ratio (the weight ratio of KOH: dried raw material), the activation temperature, and the activation time. The effect factors were investigated using Central Composite Design (CCD) software. The optimum activation conditions were found as an impregnation ratio of 1:2.6, activated time of 160 min, and temperature of 630oC. The results of the comparison show that Alhagi active carbon powder (AAC) has a high ability to develop latent fingerprints on all surfaces except on plastic surfaces while the commercial charcoal failed to develop the latent fingerprint on both plastic and aluminum foil sheets surfaces. AAC was found to clearly show every feature of the latent fingerprints more than commercial charcoal for both males and females. Also, AAC has the ability to show latent fingerprints till 15 days while commercial charcoal has the ability to show latent fingerprints just till 7 days.